Marketing Management and Strategy / 2nd Edition - Doyle Peter (Prentice Hall, 1998)
Preface, Management: Objectives and Tasks, The Customer-led Business, Segmentation and Positioning and the Marketing Mix, Strategic Market Planning, Market Dynamics and Competitive Strategy, Building Successful Brands, Innovation and New Product Development, Pricing Policy: Delivering Value, Communications Strategy, Managing Personal Selling, Managing Marketing Channels, Marketing in Service Businesses, Turnaround Management, Marketing in the Twenty-first Century, Index of Subjects.
Preface, Management: Objectives and Tasks, The Customer-led Business, Segmentation and Positioning and the Marketing Mix, Strategic Market Planning, Market Dynamics and Competitive Strategy, Building Successful Brands, Innovation and New Product Development, Pricing Policy: Delivering Value, Communications Strategy, Managing Personal Selling, Managing Marketing Channels, Marketing in Service Businesses, Turnaround Management, Marketing in the Twenty-first Century, Index of Subjects.